A Study on Diagnostic Accuracy of Dipsi Method Over Traditional Oral Glucose Tolerance Test Among Antenatal Women - Vijayadevi Shanmugam; Dharani Sudha Gopalraj; Shruthi Nanjudappan; Rajeswari Ravindran (National Board of Examinations Journal of Medical Sciences)
Introduction: Gestational diabetes mellitus (GDM) is a condition of glucose intolerance during pregnancy, with potential adverse effects on both maternal and neonatal outcomes. Detecting and treating GDM early is crucial to prevent complications. Various diagnostic criteria and methods, such as the Diabetes in Pregnancy Study Group of India (DIPSI) criteria, IADPSG (International Association of the Diabetes and Pregnancy Study Groups) have been debated for GDM screening. This study is aimed to compare the DIPSI and IADSP criteria which is widely used in India with the World Health Organization (WHO) criteria and assess their diagnostic accuracy. Methods: A cross-sectional study involving 100 antenatal mothers was conducted in a tertiary care hospital. Sociodemographic data, risk assessments, gestational age, and clinical measurements (height, weight) were collected. Participants underwent both OGTT (using WHO criteria) and DIPSI tests. The blood sugar values were classified, and diagnostic accuracy was measured using sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). The correlation between the two methods was also examined. Results: The study demonstrated a lower sensitivity, and a high specificity compared to OGTT (WHO criteria). A new cutoff of 120 mg/dl for DIPSI was obtained by ROC curve analysis for our study which had a specificity and sensitivity of 78.02% and 77.78% respectively. The correlation between OGTT fasting/postprandial and DIPSI measurements was weak. Conclusion: The study assessed the diagnostic accuracy of the DIPSI method compared to the OGTT, particularly in resource-constrained settings like India. Given the DIPSI method's observed low sensitivity, relying solely on it for GDM diagnosis is ill-advised. Failure to identify true positive cases could have significant clinical implications, impacting maternal and neonatal outcomes and overburdening healthcare systems. Further research with larger and diverse populations is needed to establish more accurate diagnostic thresholds for GDM using the DIPSI method or alternative criteria.